Gestão territorial: os vetores do desenvolvimento sustentável - Martins, Osvaldo (2013)
The study presented in this master s dissertation holds the objective of evaluating , through the existing theoretical framework on the territorial development theme, the possibility of this approach being considered as an effective, alternative form of leveraging development within its economic, social and environmental amplitudes, in order to become sustainable. Thus, a bibliographic review and a survey of secondary data was conducted, which enable an understanding of the historic process that gives origin to the situation lived by society as a whole nowadays, an understanding of how worldwide economic processes are organized, an identification of the contexts and vectors of development and how the process of territorial management should be developed in the search of results that privilege the quality of life of local societies. Special attention is given to an understanding of the vectors, which enable the process of territorial development and which were separated, for the effect of the study, in the following topics: work, job and income; organizational development; institutional development; policies and credit institutions; technology and innovation; cooperation and networks; social services and infra-structure; information and communication and environmental sustainability. In the management process, we addressed the importance of the articulation of the actors, the planning and the transparent availability of information. On analyzing the set of these vectors and processes, it is concluded that there is the need for a change in the way public management is developed, in the way companies are run and in the thinking of civil society as a whole. The logic of organizational thinking is no longer exclusively top-down, yet is also not exclusively bottom-up. Administrative decentralization and decentralization of financial resources is necessary, the territory needs to be valued and gain independence and new responsibilities, nevertheless the higher levels of government, the great movements of international regulation, in all areas, are also of fundamental importance, for no one is isolated in this world that we live in